2013
DOI: 10.1007/s00299-013-1547-6
|View full text |Cite
|
Sign up to set email alerts
|

EMS mutagenesis and qPCR-HRM prescreening for point mutations in an embryogenic cell suspension of grapevine

Abstract: Somatic embryogenesis is an excellent system for induced mutagenesis and clonal propagation in woody plants. Our work was focused on establishing a procedure for inducing ethyl methanesulfonate (EMS) mutagenesis in grapevine. Embryogenic cell aggregates (ECAs) growing in liquid medium were treated with increasing concentrations of EMS. We found that EMS dramatically affects the viability of ECAs at concentrations above 20 mM (25.5 ± 2.9 % survival), whereas concentrations above 10 mM affect embryogenic potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…2). This appears to be unique to Indel mutations because this phenomenon was never reported in HRM-TILLING studies characterizing single base-pair substitutions (Gady et al, 2009;Botticella et al, 2011;Lochlainn et al, 2011;Acanda et al, 2014;Bovina et al, 2014). However, in HRM analysis of nine Indel mutations using mixed samples, Cousins et al (2013) also observed one mutation (1-bp deletion) that performed similarly to GZ63m1 and Z9B-lpa, i.e.…”
Section: Detection Of Indel Mutations In Pooled Samplesmentioning
confidence: 66%
See 1 more Smart Citation
“…2). This appears to be unique to Indel mutations because this phenomenon was never reported in HRM-TILLING studies characterizing single base-pair substitutions (Gady et al, 2009;Botticella et al, 2011;Lochlainn et al, 2011;Acanda et al, 2014;Bovina et al, 2014). However, in HRM analysis of nine Indel mutations using mixed samples, Cousins et al (2013) also observed one mutation (1-bp deletion) that performed similarly to GZ63m1 and Z9B-lpa, i.e.…”
Section: Detection Of Indel Mutations In Pooled Samplesmentioning
confidence: 66%
“…HRM has already been widely used in plant research for high-throughput genotyping, mapping genes, and testing food products and seeds (Simko, 2016). It has also been used in combination with TILLING (HRM-TILLING) for screening EMSmutagenized populations of tomato (Gady et al, 2009), wheat (Dong et al, 2009;Lochlainn et al, 2011), and grapevine (Acanda et al, 2014). As with most other TILLING systems, HRM-TILLING has been used only for the screening of EMS-induced mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Suspension cultures can be synchronized [44] to obtain a homologous population of cells, thereby allowing experimentation on cell physiology, biochemistry, and metabolic events at the cellular level. A cell suspension culture can also aid in mutagenesis studies using CRISPR/Cas9 [45] or chemicals such as ethyl methanesulfonate [46]. The only downside to the system proposed here is that plant regeneration cannot occur directly from suspension cultures, which requires an extra solidified tissue culture step prior to plant regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was observed in more than 15 plant species [4]. Moreover, Acanda et al [18] found that these transitions caused multiple alleles within a gene, leading to multiple phenotypes. Point mutations occur in the exonic regions [19], with higher methylation rates in the 5' regions [20].…”
Section: Mechanisms Of Action Of Emsmentioning
confidence: 89%